Serovar-dependent differences in Hfq-regulated phenotypes in Actinobacillus pleuropneumoniae. - Crispim,JS; da,Silva TF; Sanches,NM; da,Silva GC; Pereira,MF; Rossi,CC; Li,Y; Terra,VS; Vohra,P; Wren,BW; Langford,PR; Bossé,JT; et al. (Pathogens and Disease, 2020)
The RNA chaperone Hfq regulates diverse processes in numerous bacteria. In this study, we compared phenotypes (growth rate, adherence, response to different stress conditions, and virulence in Galleria mellonella) of wild-type (WT) and isogenic hfq mutants of three serovars (1, 8 and 15) of the porcine pathogen A. pleuropneumoniae. Similar growth in rich broth was seen for all strains except Ap1hfq, which showed slightly reduced growth throughout the 24 hour time course, and the complemented Ap8hfqC mutant had a prolonged lag phase. Differences were seen between the three serovar WT strains regarding adherence, stress response and virulence in G. mellonella, and deletion of hfq affected some, but not all of these phenotypes, depending on serovar. Complementation by expression of cloned hfq from an endogenous promoter only restored some WT phenotypes, indicating that complex regulatory networks may be involved, and that levels of Hfq may be as important as presence/absence of the protein regarding its contribution to gene regulation. Our results support that Hfq is a pleiotropic global regulator in A. pleuropneumoniae, but serovar-related differences exist. These results highlight the importance of testing multiple strains/serovars within a given species when determining contributions of global regulators, such as Hfq, to expression of complex phenotypes.